Canadian refugee resettlement: a case study of the process of policy-making for Iraqi refugees - Gauthier, Mia (AUC Knowledge Fountain, 2010)
The purpose of this research is to understand how the Canadian government came to decide when was the opportune time to begin the resettlement of Iraqis, what magnitude these resettlement operations would take, and whom, amongst the millions of Iraqis displaced by the war following the 2003 U.S.-led invasion, would be selected for resettlement to Canada. The research identifies different sets of influences on the policy-making process related to the resettlement of Iraqi refugees to Canada, and explores how these resettlement policies were initiated, developed, implemented, and shaped over time. A literature review is undertaken on the history of the rationale supporting the use of resettlement as a possible durable solution to refugee crises. Expert interviews were conducted with representatives of the Government of Canada, UNHCR Ottawa, Amnesty International Canada, the Canadian Council for Refugees, Iraqi community organizations in Canada, and other experts in the field, in order to collect factual accounts, as well as personal and institutional perspectives on the topic. It was found that the most delimiting factor was the budget allocated to the resettlement program, determined by the Canadian Parliament. In turn, the Parliament was said to be most influenced, on the one hand, by the insistently expressed opinions of Canadian voters, and, on the other, by the necessity to retain Canada's humanitarian image. Where and how the budget is spent is highly dependent upon the directives of UNHCR. The budget is also allocated strategically in order to maximize the leverage of resettlement operations for all those affected â refugee populations and asylum countries alike.